Comorbidity of fetal alcohol spectrum disorder: a systematic review and meta-analysis. Issue 10022 (5th March 2016) - Popova, Svetlana; Lange, Shannon; Shield, Kevin; Mihic, Alanna; Chudley, Albert E; Mukherjee, Raja A S; Bekmuradov, Dennis; Rehm, Jürgen
Summary: Background: Fetal alcohol spectrum disorder (FASD) is related to many comorbidities because of the permanent effects of prenatal alcohol exposure on the fetus. We aimed to identify the comorbid conditions that co-occur in individuals with FASD and estimate the pooled prevalence of comorbid conditions occurring in individuals with fetal alcohol syndrome (FAS). Methods: We did a systematic literature search of studies reporting on the comorbidity and cause of death in individuals with FASD using multiple electronic bibliographic databases, searching for studies published up to July, 2012. We included original research published in a peer-reviewed journal in the English language. We used the following criteria for determining study quality: use of an established FASD diagnostic guideline, study setting, method of data collection, and sample size. All comorbid disease conditions were coded according to the International Classification of Diseases, tenth revision (ICD-10). To estimate the pooled prevalence of comorbid conditions found to co-occur in individuals with FAS, we did meta-analyses assuming a random-effects model. Findings: Of 5068 studies found, 127 met eligibility criteria for data extraction. From those studies, we identified 428 comorbid conditions co-occurring in individuals with FASD, spanning across 18 of 22 chapters of the ICD-10. The most prevalent disease conditions were within the sections of congenital malformations, deformities, and chromosomal abnormalities, and mental and behavioural disorders. 33 studies reported data for frequency in a total of 1728 participants with FAS. The five comorbid conditions with the highest pooled prevalence (between 50% and 91%) included abnormal results of function studies of peripheral nervous system and special senses, conduct disorder, receptive language disorder, chronic serous otitis media, and expressive language disorder. Interpretation: The high prevalence of comorbid conditions in individuals with FASD highlights the importance of assessing prenatal alcohol exposure as a substantial clinical risk factor for comorbidity. The harmful effects of alcohol on a developing fetus represent many cases of preventable disability, and thus, alcohol use during pregnancy should be recognised as a public health problem globally. Funding: Public Health Agency of Canada.